Optimizing Third-Party Funds through SimPel Savings: A Financial Inclusion Strategy among Students - Argantara, Zaid Raya; Safitri, Annisa Windiyah; Zaidiah, Zaidiah; Aisyah, Aisyah (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze strategies for increasing the amount of DPK through the Simpel Savings program at BPRS Bhakti Sumekar, Pragaan Branch Office. The research employs a descriptive qualitative method, with data collected through observation, interviews, and document analysis. Data were analyzed using the interactive model of Miles and Huberman, consisting of data presentation, data reduction, and conclusion drawing. The findings indicate that the strategy for increasing DPK through Simpel Savings is implemented through four main approaches: (1) financial literacy outreach in schools, (2) easy access to savings services within the school environment, (3) active collaboration with schools and parents, and (4) simplification of account opening procedures. These strategies have proven effective in increasing the number of student customers and total collected funds, as well as in strengthening the culture of saving and Islamic financial literacy from an early age. This study contributes to enriching the literature on DPK mobilization strategies in Islamic banking through literacy- and inclusion-based approaches targeting students.